Biopolymers in the preservation of rhizobacteria cells and efficiency in soybean inoculation (Research, Society and Development, 2022)
Soybean (Glycine max (L). Merr.) is among the most important legumes worldwide performing a significant role in biological fixation of nitrogen through rhizobacteria. These microorganisms that act in the plant root system are inoculated by biological products, which must contain viable cells. The viability of inoculants is a market challenge, and biopolymers have been studied for the preservation of microorganisms. Thus, this study aimed to assess the influence of adding xanthan gum and carboxymethylcellulose biopolymers on the preservation of cells of Bradyrhizobium elkanii, Bradyrhizobium diazoefficiens, Azospirillum sp., and Pseudomonas fluorescens, and inoculation of soybean seeds. The inoculants were produced and stored added with biopolymers. Soybean seeds were inoculated at 0, 90 and 210 inoculant storage days and sown in pots of 1 L. 50 days after emergence for assessing physiological parameters of stomatal conductance (gs - mol H20 m-2 s-1), CO2 assimilation rate (A - µmol CO2 m-2 s-1), transpiration rate (E - mmol H2O m-2 s-1), in addition to morphological parameters of plant height (H), fresh mass of aerial part (FMAP), root fresh mass (RFM), number of nodules (NNo), fresh mass of nodules (FMNo), dry mass of aerial part (DMAP), root dry mass (RDM), and dry mass of nodules (DMNo). The use of biopolymers proved efficient at preserving the cells of the microorganisms tested at 210 storage days through the responses obtained from an increase in aerial and root plant biomass resulting from a more efficient nodulation in the inoculant with biopolymer.